PERKEMBANGAN PEMBUKTIAN PADA PUTUSAN VERSTEK: STUDI KASUS DI PENGADILAN NEGERI SLEMAN DAN KOTA YOGYAKARTA - Sundari, Elisabeth; Widiastiani, Nindry Sulistya (Justitia et Pax, 2019)
Article 25 of HIR provides that in case the defendant does not appear at court process (verstek), the claim will be accepted unless it is unreasonable and against the rights. In the beginning, that article was interpreted that in case the defendant doesn’t  appear at court process (verstek), the plaintiff shall not obeyed to proof his claim. How is the development of that previous interpretation? Normative legal research has been conducted to redress that issue. The data were collected from secondary data resources from Sleman and Yogyakarta District Court decisions concerning the burden of proof  in verstek recently,  and being  analized  qualitatively. The research result shows that there is a development in  interpretating Article 125 HIR, where the judges burdened the plaintiff to proof his claim. That interpretation development supports the strive to get the truth beyond reasonable doubt, to meet a fair decision,  as good as to avoid fraud claim, and haphazard decision.